Cooking up a storm: Community-led mapping and advocacy with food vendors in Nairobi's informal settlements - Ahmed, S.; Simiyu, E.; Githiri, G.; Sverdlik, A.; Mbaka, S. (International Institute for Environment and Development, 2015)
Food security is rarely prioritised in African cities, and food vendors are similarly ignored or stigmatised, despite providing a range of affordable, accessible meals. Furthermore, past research and urban policies usually overlook food hawkers selling inside informal settlements. Based on participatory research in Nairobi, this paper aims to address the invisibility of vendors in informal settlements and to inform more appropriate, inclusive urban food security strategies. Balloon-mapping and other novel mapping techniques were combined with focus group discussions to explore vendors’ practices, challenges, and opportunities for promoting food safety. Our detailed maps, vivid narratives, and community-led strategies may cook up a storm that can create safer foods and more secure livelihoods, with benefits extending across African informal settlements.